Research trends in the effect of caffeine intake on fat oxidation: a bibliometric and visual analysis - Gutiérrez-Hellín, J.; Del Coso, J.; Espada, M. C.; Hernández-Beltrán, V.; Ferreira, C. C.; Varillas-Delgado, D.; Mendoza Laiz, N.; Roberts, J. D.; Gamonales, J. M. (Nutrients, 2023)
In the last few decades, numerous studies pertaining to research groups worldwide have investigated the effects of oral caffeine intake on fat oxidation at rest, during exercise, and after exercise. However, there is no bibliometric analysis to assess the large volume of scientific output associated with this topic. A bibliometric analysis of this topic may be used by researchers to assess the current scientific interest in the application of caffeine as a nutritional strategy to augment fat oxidation, the journals with more interest in this type of publication, and to draw international collaborations between groups working in the same area. For these reasons, the purpose of this study was to assess the research activity regarding oral caffeine intake and fat oxidation rate in the last few decades by conducting a bibliometric and visual analysis. Relevant publications from 1992 to 2022 were retrieved from the Web of Science (WoS) Core Collection database. Quantitative and qualitative variables were collected, including the number of publications and citations, H-indexes, journals of citation reports, co-authorship, co-citation, and the co-occurrence of keywords. There were 182 total publications, while the number of annual publications is saw-shaped with a modest increase of 11.3% from 2000 to 2009 to 2010 to 2019. The United States was the country with the highest number of publications (24.17% of the total number of articles), followed by the Netherlands (17.03%). According to citation analyses, the average number of citations per document is 130, although there are 21 documents that have received more than 100 citations; the most cited document reached 644 citations. These citation data support the overall relevance of this topic in the fields of nutrition and dietetics and sport sciences that when combined harbored 85.71% of all articles published in the WoS. The most productive author was Westerterp-Plantenga with 16 articles (8.79% of the total number of articles). Nutrients was the journal that published the largest number of articles on this topic (6.59% of the total number of articles). Last, there is a tendency to include keywords such as "performance", "carbohydrate", and "ergogenic aid" in the newer articles, while "obesity", "thermogenic", and "tea" are the keywords more commonly included in older documents. Although research into the role of caffeine on fat oxidation has existed since the 1970s, our analysis suggests that the scientific output associated with this topic has progressively increased since 1992, demonstrating that this is a nutritional research area with a strong foundational base of scientific evidence. Based on the findings of this bibliometric analysis, future investigation may consider focusing on the effects of sex and tolerance to caffeine to widen the assessment of the effectiveness of oral caffeine intake as a nutritional strategy to augment the use of fat as a fuel, as these terms rarely appear in the studies included in this analysis. Additionally, more translational research is necessary as the studies that investigate the effect of oral caffeine intake in ecologically valid contexts (i.e., exercise training programs for individuals with excessive adiposity) are only a minor part of the studies on this topic.